Electromagnetic interactive module (MI-EM) / Hazimah Ashamuddin ... [et al.] - Ashamuddin, Hazimah; Nuruddin, Nur’Ainiza; Mohd Zahar, Mohd Izzat Iqbal; Yap Abdullah, Nurul Syafiqah; Mat Darus, Mazlina (2020)
Utilization of innovation in teaching and learning is common in the field of e-learning, including learning Physics. Electromagnetic was one of the most challenging subjects in Physics as most students had difficulty visualizing the abstract concept in this topic and often leading to misconception when using books. Several innovations have been done on learning Electromagnetic through technology that are more efficient, exciting, and vibrant such as a smartphone. An empirical study was carried out among Matriculation Physic lecturers to determine the need to develop a module for matriculation’s students and recommend input in preparing the module. Therefore, an invention of the Electromagnetic Induction Module (MI-EM) has been developed in the Electromagnetic Topic for matriculation students as a selflearning to help them learn anytime, anywhere and increase their understanding on the topic. MI-EM module is an interactive module that was developed using Moodle platform. Varied software and websites created all the elements in the MI-EM module as interactive elements. The students from Selangor Matriculation College and Melaka Matriculation College were given pre-tests and post-tests to evaluate the efficacy of the MI-EM Module. The findings indicate that the MI-EM module helped students to increase their understanding of the topic.